2011
DOI: 10.1089/ars.2010.3811
|View full text |Cite
|
Sign up to set email alerts
|

The Multidomain Thioredoxin-Monothiol Glutaredoxins Represent a Distinct Functional Group

Abstract: Monothiol glutaredoxins (Grxs) with a noncanonical CGFS active site are found in all kingdoms of life. They include members with a single domain and thioredoxin-Grx fusion proteins. In Saccharomyces cerevisiae, the multidomain Grx3 and Grx4 play an essential role in intracellular iron trafficking. This crucial task is mediated by an essential Fe/S cofactor. This study shows that this unique physiological role cannot be executed by single domain Grxs, because the thioredoxin domain is indispensable for function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
45
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 67 publications
0
45
0
Order By: Relevance
“…Mutational analysis of the Cys35 residue located within the TRX domain of Grx4 revealed that it is required for the establishment of a strong, iron-independent association with Fep1 (17). Consistently, a recent study of S. cerevisiae suggested that the TRX domain may serve as a docking site for the interacting partners of the multidomain monothiol glutaredoxins Grx3 and Grx4 (12). In baker's yeast, other functions for the TRX domain have been proposed, including a role in the targeting of the monothiol glutaredoxin Grx3 to the nucleus (31), as well as a regulatory role in actin cytoskeleton remodeling and a role in cellular defense against oxidative stress (40).…”
mentioning
confidence: 65%
“…Mutational analysis of the Cys35 residue located within the TRX domain of Grx4 revealed that it is required for the establishment of a strong, iron-independent association with Fep1 (17). Consistently, a recent study of S. cerevisiae suggested that the TRX domain may serve as a docking site for the interacting partners of the multidomain monothiol glutaredoxins Grx3 and Grx4 (12). In baker's yeast, other functions for the TRX domain have been proposed, including a role in the targeting of the monothiol glutaredoxin Grx3 to the nucleus (31), as well as a regulatory role in actin cytoskeleton remodeling and a role in cellular defense against oxidative stress (40).…”
mentioning
confidence: 65%
“…Importantly, the recognition of Aft1 involves at least a negatively charged region in the yeast Grx4 formed by the last 16 C-terminal residues (supplemental Fig. S2) (40). Overall, although it is not clear where the Grx-BolA complex is acting, it is very likely that the formation of the Fe-S cluster in the Grx-BolA heterodimer is crucial for Aft1 regulation.…”
Section: Rieske-type [2fe-2s] Coordination Occurs In Grx-bola_hmentioning
confidence: 99%
“…2). The latter proteins occur almost exclusively in eukaryotes and represent a distinct functional group (35).…”
Section: Fig 2 Sequence Analysis Of Monothiol Glutaredoxins (A)mentioning
confidence: 99%
“…Instead, the capability to coordinate ISCs appears to be a common feature for 1-C-Grxs (16,40,42,43,54,67,89) with yeast Grx7 being, so far, the only known exception (59,60). The latter feature determines an evolutionary conserved and indispensable role of 1-C-Grxs in the biogenesis and assembly of iron-sulfur proteins (11,61) and other cell-specific regulatory functions such as the (in)activation of nuclear transcription factors (35,62,86).…”
Section: Fig 2 Sequence Analysis Of Monothiol Glutaredoxins (A)mentioning
confidence: 99%
See 1 more Smart Citation